Molecular study of selected differentially expressed genes in nasopharyngeal carcinoma - Chua, Suk Ngo (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Nasopharyngeal Carcinoma (NPC) occurs as a consequence of multiple molecular events induced by environmental factors and Epstein-Barr virus (EBV) infections. The neoplastic processes may involve alterations of the tumor suppressor genes and oncogenes by genetic damage and interference with the normal cellular functions by the EBV latent gene products. Overexpression of TNF receptor-associated factor 6 (TRAF6) has been reported to suppress orilP activity and loss of EBV from Burkitt's lymphoma cell line. The role of vigilin in cytoplasmic mRNA metabolism has been suggested whereby alterations in mRNA regulation by RNA binding protein have been reported in diverse cancer types.